대한민국 청소년의 주간 졸음증에 관련된 요인 분석 - 장은정; 김정선; 김기태; 곽혜선; 한지민; Eun Jeong Jang; Jung Sun Kim; Kitai Kim; Hye Sun Gwak; Ji Min Han (한국임상약학회지, 2024)
Background: Daytime sleepiness, a common phenomenon among adolescents focused on academics, has negative effects on aspects such as growth and overall learning. However, research on various drugs and diseases affecting daytime sleepiness is lacking in the reality. Therefore, this study aims to investigate the factors influencing daytime sleepiness in adolescents with daytime sleepiness. Methods: This study was conducted through a survey of 2,432 middle and high school students, aged 14 to 19. The questionnaire consisted of information on socio-demographic characteristics, overall health status, and sleep patterns. The Pediatric Daytime Sleepiness Scale (PDSS), translated into Korean, was used to assess daytime sleepiness. Daytime sleepiness was measured by calculating the total score for each item of the PDSS, and divided into two groups based on the cutoff value of 19, which was the upper quartile. Results: We analyzed a total of 1,770 students including 799 boys and 971 girls. Students with a PDSS score of 19 or higher made up 33.3% of boys and 66.7% of girls. In multivariate analyses, females, smoking, poor self-reported health level, sleep after 12 am, not feeling refreshed in the morning, headache, muscle pain, and scoliosis increased the risk of daytime sleepiness significantly. The AUROC of PDSS, including significant factors in multivariate analyses, was 0.751 (95% CI 0.725~0.776). Conclusions: Daytime sleepiness in adolescents affects growth, academic performance, and emotional stability. Therefore, it is important to manage medications, diseases, and other factors that affect daytime sleepiness on a social level.